2014
DOI: 10.5585/conssaude.v13n1.4607
|View full text |Cite
|
Sign up to set email alerts
|

Comparação da qualidade de vida em mulheres praticantes de Pilates e musculação

Abstract: Objetivo: Comparar o nível de qualidade de vida e a percepção de saúde física e mental de mulheres na meia-idade, praticantes de musculação e do método Pilates, a fim de verificar qual treino associa-se com melhores níveis de qualidade de vida nessa amostra. Métodos: Foram incluídas 50 mulheres na meia-idade divididas em dois grupos com 25 integrantes, sendo um grupo de praticantes do método Pilates (50,53±4,3 anos), e o outro, de musculação (50,4±5,2 anos). Foram aplicados o questionário de qualidade de vida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…One study evaluated the effects of Pilates on a sample of 47 adults, male and female, for a period of 6 months on the criteria: flexibility, body composition and general health status; and the results showed that there was no statistically significant change in these domains between the time, however, the study did not have control group and consequently, there was no comparison between the groups (12) . Other authors did not find a statistically significant difference between groups for the general health domain of SF-36 among a group of women who practice Pilates and a bodybuilding group (13) . This study also did not have a control group.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…One study evaluated the effects of Pilates on a sample of 47 adults, male and female, for a period of 6 months on the criteria: flexibility, body composition and general health status; and the results showed that there was no statistically significant change in these domains between the time, however, the study did not have control group and consequently, there was no comparison between the groups (12) . Other authors did not find a statistically significant difference between groups for the general health domain of SF-36 among a group of women who practice Pilates and a bodybuilding group (13) . This study also did not have a control group.…”
Section: Discussionmentioning
confidence: 87%
“…In the study that also evaluated quality of life, it was verified that the score of the emotional aspects were statistically better in the Pilates group than in the bodybuilding group (13) . The present study agrees with a research that associated positive change in the emotional aspects domain with the practice of the Pilates Method, which leads us to think that if performed regularly and following the basics, the Pilates method can contribute to changes in the quality of life of the individual (20) .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…According to Lara, Wendet and Silva (2014), who conducted a study with 50 women aged between 45 and 55 years old, divided into two groups of 25 participants each, one group underwent weight training and the second group participated in training sessions. Pilates, both twice a week for six months, at the end of the study found that the two methods positively affected the muscle strength and quality of life of the participants, but weight training was superior mainly in the postural aspect and perception of mental health.…”
Section: Resultsmentioning
confidence: 99%
“…There are studies on, among other topics, balance and strength (3), lexibility (4), pain (6), spinal mobility and pulmonary function (7), quality of life (8), body composition (9), functional capacity (10), and bone remodeling (10). However, most publications address the effect of the Pilates method for treating low back pain (11).…”
Section: Introductionmentioning
confidence: 99%